Implementasi Sistem Informasi Manajemen Paket Aplikasi Sekolah (SIM-PAS) di SD Sekecamatan Kei Kecil Kabupaten Maluku Tenggara - Munipah, Siti; Rahabav, Patris; Sahallesy, Arnold; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Management information systems in education are a series of links between human resources and information technology applications that are used to store, process and retrieve data in order to support the decision-making process in the field of education. This research aims to determine the implementation and level of effectiveness of the school package management information system as well as supporting and inhibiting factors in the use of the SIM-PAS school application in elementary schools in Kei Kecil District, Southeast Maluku Regency. The method used in this research is a qualitative descriptive method, using observation techniques, interviews, documentation and data analysis techniques through data collection, data reduction, data display and conclusion drawing. /verification). The results of the research show that the role of all stackholders in developing the implementation of the school application package management information system (SIM-PAS) in elementary schools in Kei Kecil District is really needed starting from planning, organizing, controlling and directing in developing the use of the assessment application package management information system in order to create change and can impart the knowledge they have to other schools in Southeast Maluku Regency.